Antimicrobial therapy and assessing therapeutic response in culture-negative pyogenic vertebral osteomyelitis: a retrospective comparative study with culture-positive pyogenic vertebral osteomyelitis - Dongwoo Yu; Sang Woo Kim; Ikchan Jeon (BMC Infectious Diseases, 2020)
Abstract Background There are still controversies regarding the treatment and outcomes in culture-negative pyogenic vertebral osteomyelitis (PVO). The purpose of this study is to investigate the antimicrobial therapy, assessment of therapeutic response, and outcome of culture-negative PVO compared to culture-positive PVO. Methods A retrospective study was performed with non-surgical lumbar PVO patients. The patients were divided into two groups based on the causative bacterial identification (CN group with culture-negative PVO and CP group with culture-positive PVO). The clinical features, use of antibiotics, laboratory data, and outcomes were compared between the two groups. Results Seventy-three patients with 41 (56.2%) of the CN group and 32 (43.8%) of the CP group were enrolled. The CN group showed a shorter duration of parenteral antibiotics (45.88 ± 16.14 vs. 57.31 ± 24.39, p = 0.019) but a tendency of prolonged duration of total (parenteral + oral) antibiotics (101.17 ± 52.84 vs. 84.19 ± 50.29 days, p = 0.168). When parenteral antibiotics were discontinued or switched to oral antibiotics, the mean erythrocyte segmentation rate (ESR, normal range: < 25 mm/h), C-reactive protein (CRP, normal range: < 0.5 mg/dL) level, and visual analog scale (VAS) score of back pain were 42.86 ± 24.05 mm/h, 0.91 ± 1.18 mg/dL, and 4.05 ± 1.07, respectively, with no significant differences between the two groups. The recurrence rates of CN and CP groups were 7.3% (3/41) and 6.3% (2/32), respectively (p = 1.000). The presence of epidural abscess was the most significant factor for the identification of causative bacteria (p = 0.002), and there was no significant relationship between the use of empirical antibiotics before tissue culture and the causative bacterial identification (p = 0.194). Conclusions The CN group required a shorter duration of parenteral antibiotics than the CP group. Discontinuation of parenteral antibiotics or changing the administration route can be considered based on the values of ESR, CRP, and VAS score of back pain. The presence of epidural abscess was the most significant factor for the identification of causative bacteria.